Emotions, technology, and health - Tettegah, Sharon Y.; Garcia, Yolanda Evie (Academic Press, 2016)
Emotions, Technology, and Health examines how healthcare consumers interact with health technology, how this technology mediates interpersonal interactions, and the effectiveness of technology in gathering health-related information in various situations. The first section discusses the use of technology to monitor patients' emotional responses to illness and its treatment, as well as the role of technology in meeting the fundamental human need for information. Section Two describes the use of technology in mediating emotions within and between individuals, and addresses the implications for the design and use of devices that gather behavioral health data and contribute to healthcare interventions. The final section assesses different situations in which technology is a key component of the health intervention-such as tablet use in educating elementary school students with social skills difficulty, physical activity monitoring for children at risk for obesity, and teleconferencing for older adults at risk of social isolation
Includes bibliographical references
Keywords: PSYCHOLOGY / Physiological Psychology; Emotions / Health aspects; Technology / Psychological aspects; Biomedical Technology; Emotions -- Health aspects; Technology -- Psychological aspects; Embodiment; Gefühl; Mensch-Maschine-Kommunikation